The multidimensional nature of social capital: an empirical investigation for older people in Europe - Gannon, Brenda; Roberts, Jennifer (Sheffield, 2014)
"Social capital is a rapidly expanding research theme within economics and has become a popular concept with policy makers in both developed and developing countries. Despite this growth in popularity, social capital remains a controversial concept among economists. We argue that this is largely due to a fundamental mismatch between the theoretical coverage and the vast majority of empirical work. Utilising data from a large cross-Europe survey of older people we use principal components analysis to demonstrate that social capital has multiple dimensions, and then explore the extent to which these latent dimensions coincide with the theoretical constructs of social capital. We use the association between social capital and a number of measures of health and well-being to demonstrate the importance of taking account of the multiple dimensions of social capital in empirical work. As well as showing that all the underlying constructs of social capital are significantly associated with health and well-being, our results also reveal that while in general this association is positive, close bonding in the form of household ties is inversely related to health and well-being; this contradicts the implicit assumption, often made in the literature that, in relation to social capital, more is always better."